Potential therapeutic strategies for colitis and colon cancer: bidirectional targeting STING pathway - Jiaorong Qu; Yajie Cai; Fanghong Li; Xiaojiaoyang Li; Runping Liu (EBioMedicine)
Summary: The cyclic-GMP-AMP synthase (cGAS)-stimulator of interferon gene (STING) pathway has emerged as a promising therapeutic target for colitis and colon cancers. Notably, inhibiting STING may mitigate the progression of colitis, whereas activating STING can enhance anti-tumor immune responses against colon cancer. This duality suggests that the development of STING agonists and inhibitors possesses significant clinical translational potential. In this review, we provide a comprehensive overview of STING inhibitors/agonists that have been systematically evaluated in the contexts of colitis and colon cancer and their specific molecular mechanisms. Other well-characterized STING inhibitors/agonists may also hold considerable promise for the treatment of these conditions, although efficacy validation remain necessary. Additionally, we delve into the latest advances concerning STING oligomerization, degradation and phase separation-dependent self-regulation, proposing potential druggable targets that could inspire the development of novel STING agonists or inhibitors. In Summary, targeting STING appears to be a promising strategy for the treatment of colitis and colon cancer.